Partner Services as Targeted HIV Screening—Changing the Paradigm. (January 2014) - Bernstein, Kyle T.; Stephens, Sally C.; Moss, Nicholas; Scheer, Susan; Parisi, Maree Kay; Philip, Susan S.
Objectives: The San Francisco Department of Public Health (SFDPH) has the goal of offering HIV partner services (PS) to all individuals newly diagnosed with HIV in San Francisco. However, measuring the potential impact of these services is challenging. Building on an existing syphilis partner notification program, we developed a framework for expanding and monitoring HIV PS in San Francisco. Methods: We identified process and outcome measures to evaluate HIV PS in San Francisco, including the number of index patients interviewed, the proportion of named partners who had previously diagnosed HIV infection, the proportion of HIV-uninfected partners who tested through HIV PS, and the positivity rate among the partners tested. Results were recorded in a locally developed electronic surveillance and case-management system at SFDPH. Results: We examined HIV PS data from 2005–2011. In 2011, 426 new HIV diagnoses were reported, and 178 were assigned for HIV PS; of these, 124 (69.7%) patients were successfully interviewed, naming a total of 109 sex partners. Of the named partners, 34 (31.2%) had been previously diagnosed with HIV. Among the remaining named partners not known to be HIV infected, 31 (32.3%) were tested, for a positivity of 22.6% (n=7). The proportion of HIV that was newly diagnosed by a provider who participated in the citywide HIV PS program increased from 15.4% in 2005 to 69.5% in 2011. Conclusions: As HIV PS expand, locally relevant outcome measures are increasingly important. Using these criteria, HIV PS as a targeted screening activity resulted in the identification of newly diagnosed HIV cases.